Pengaruh Pendekatan Open-Ended dengan Pembelajaran Kooperatif Tipe STAD terhadap Kemampuan Pemahaman dan Koneksi Matematis Siswa Ditinjau dari Self-Efficacy: Eksperimen di SMK Negeri 9 Kota Bekasi - Nurimani N (LPPM STKIP Kusuma Negara, 2016)
This study aims to determine the effect of open-ended approach with STAD cooperative learning on the ability of understanding and connection of mathematics students in terms of self-efficacy. The study was conducted in SMK Negeri 9 Kota Bekasi using the experiments conducted to 54 students. Retrieval of data obtained through a questionnaire and analyzed using ANOVA two-lane design with treatment by level. The results showed that, (1) there is no difference in the ability of students' understanding of mathematics that uses open-ended approach with STAD cooperative learning and teaching expository, (2) there is no interaction effects of self-efficacy and implementation of cooperative learning type STAD with open-approach ended the ability of understanding of mathematics, (3) there is no difference in the ability to connect math students who use open-ended approach with STAD cooperative learning and teaching expository, (4) there are interaction effects of self-efficacy and implementation of cooperative learning type STAD with open-approach ended on connection capability math student, (5) the group of students who have self-efficacy is high, there is no difference in the ability to connect math students who approach the open-ended with STAD cooperative learning and teaching expository, (6) in the group of students who have Low self-efficacy, the ability to connect math students who use open-ended approach to expository better than STAD cooperative learning.